Nubian Women of West Aswan - Jasper, Kata (Afrika Tanulmányok / Hungarian Journal of African Studies, 2011)
Jasper Kata a következő művet mutatta be: Anne M. Jenning: Nubian Women of West Aswan: Negotiating Tradition and Change. The American University in Cairo Press, Cairo, 2009